Glassy carbon electrodes modified with multiwall carbon nanotubes dispersed in polylysine - Jalit, Yamile (2008)
We report the analytical performance of glassy carbon electrodes (GCE) modified with a dispersion of multi-wall carbon nanotubes (MWCNT) in polylysine (Plys) (GCE/MWCNT-Plys). The resulting electrodes show an excellent electrocatalytic activity towards different bioanalytes like ascorbic acid, uric acid and hydrogen peroxide, with important decrease in their oxidation overvoltages. The dispersion of 1.0 mg/mL MWCNT in 1.0 mg/mL polylysine is highly stable, since after 2 weeks the sensitivity for hydrogen peroxide at GCE modified with this dispersion remained in a 90 % of the original value. The MWCNT-Plys layer immobilized on glassy carbon electrodes has been also used as a platform to build supramolecular architectures by self-assembling of polyelectrolytes based on the polycationic nature of the polylysine used to disperse the nanotubes. The self-assembling of glucose oxidase has allowed us to obtain a supramolecular multistructure for glucose biosensing. The influence of glucose oxidase concentration and adsorption time as well as the effect of using polylysine or MWCNT-Plys as polycationic layers for further adsorption of GOx is also evaluated.